Haplotypes of the estrogen receptor beta gene and breast cancer risk. - Cox, D; Bretsky, P; Kraft, P; Pharoah, P; Albanes, D; Altshuler, D; Amiano, P; Berglund, G; Boeing, H; Buring, J; Burtt, N; Calle, E; et al. (2008)
Exposure to exogenous (oral contraceptives, postmenopausal hormone therapy) and endogenous (number of ovulatory cycles, adiposity) steroid hormones is associated with breast cancer risk. Breast cancer risk associated with these exposures could hypothetically be modified by genes in the steroid hormone synthesis, metabolism and signaling pathways. Estrogen receptors are the first step along the path of signaling cell growth and development upon stimulation with estrogens. The National Cancer Institute Breast and Prostate Cancer Cohort Consortium has systematically selected haplotype tagging SNPs in genes along the steroid hormone synthesis, metabolism and binding pathways, including the estrogen receptor beta (ESR2) gene. Four htSNPs tag the 6 major (>5% frequency) haplotypes of the ESR2 gene. These polymorphisms have been genotyped in 5,789 breast cancer cases and 7,761 controls nested within the American Cancer Society Cancer Prevention Study II, European Prospective Investigation into Cancer and Nutrition, Multiethnic Cohort, Nurses' Health Study and Women's Health Study cohorts. None of the SNPs were independently associated with breast cancer risk. One haplotype of the ESR2 gene was associated with breast cancer risk before correction for multiple testing (OR 1.17, 95% CI 1.07-1.28, p = 0.0007). This haplotype remained associated with breast cancer risk after adjustment for multiple testing using a permutation procedure. There was no statistically significant heterogeneity in SNP or haplotype odds ratios across cohorts. These data suggest that inherited variants in ESR2 (while possibly conferring a small increased risk of breast cancer) are not associated with appreciable (OR > 1.2) changes in breast cancer risk among Caucasian women.